(untitled) (Swiss Medical Weekly, 2016)
Foxp3+ regulatory T cells (Tregs) maintain immune tolerance, prevent autoimmunity and modulate immune responses during infection and cancer. Recent studies have revealed considerable heterogeneity and plasticity within the Treg compartment, depending on the immunological context, which may result in Tregs losing their suppressive function in inflammatory environments. We review how dysfunctional Tregs contribute to disease pathogenesis in inflammatory conditions and how inappropriate regulatory responses may hamper protective immunity in the context of infection and cancer. We also discuss how Tregs might be targeted therapeutically to re-establish a proper balance between regulatory and effector responses in autoimmunity, infections, and cancer.